Encoding-independent optimization problem formulation for quantum computing - Dominguez, Federico; Unger, Josua; Traube, Matthias; Mant, Barry; Ertler, Christian; Lechner, Wolfgang (Frontiers in Quantum Science and Technology, 2023)
We review encoding and hardware-independent formulations of optimization problems for quantum computing. Using this generalized approach, an extensive library of optimization problems from the literature and their various derived spin encodings is discussed. Common building blocks that serve as a construction kit for formulating these spin Hamiltonians are provided. This previously introduced approach paves the way towards a fully automatic construction of Hamiltonians for arbitrary discrete optimization problems and this freedom in the problem formulation is a key step for tailoring optimal spin Hamiltonians for different hardware platforms.